Antipsychotic-induced hyperprolactinemia: Toxicologic mechanism and the increased breast cancer risk - Steven B. Bird (Toxicology Reports)
Antipsychotic drugs are effective at improving both the positive and negative symptoms of schizophrenia as well as the manic phase of bipolar disorder. Whether an antipsychotic is termed typical or atypical is related to the xenobiotic’s propensity to cause extrapyramidal side effects. However, with a few exceptions, drugs of both classes of antipsychotics are known to cause hyperprolactinemia. As many breast cancers are responsive to prolactin concentrations, the persistent increase in prolactin of the antipsychotics has implications for public health and carcinogenesis. The objective of this study was to review the extant literature on hyperprolactinemia due to antipsychotics, and to determine the risk imposed by those drugs on human breast cancer. A summary risk of breast cancer with use of any antipsychotic was found to be 1.19 (95 % confidence interval 1.10–1.30). When limiting usage of antipsychotics to 5 or more years, the summary risk increased to 1.26 (95 % confidence interval 1.12–1.43). And when limited to those studies who evaluated only those medications with the greatest increase in prolactin, the risk increased to 1.59 (95 % confidence interval 1.37–1.85). Given this increased risk of breast cancer, stronger warnings about this increased risk are warranted, and regular monitoring of prolactin levels and breast cancer screening should be part of the management plan for these patients.